Barriers and Facilitators to Colorectal Cancer Screening Among Health Fair Attendees in Utah - Jordan E. Johnson; Svenja Pauleck; Andrea J.H. Williamson; Maranda Pahlkotter; Federica S. Brecha; Nathaniel Ferre; Nancy Ortiz; Robin L. Marcus; Sheetal Hardikar; Jessica N. Cohan (Journal of Primary Care & Community Health, 2025)
Background: Colorectal cancer (CRC) screening uptake remains suboptimal despite the importance and effectiveness of various testing options. The purpose of our study was to identify barriers and facilitators to CRC screening in a community-based sample in Salt Lake County, Utah to inform future efforts to develop effective interventions to increase CRC screening. Methods: This study enrolled adults eligible for CRC screening at 6 community health events. Participants completed targeted questionnaires based on whether they had discussed screening with a provider and whether they had received screening. We identified participant-reported barriers to CRC screening using descriptive analysis. Univariate and multivariate analyses were used to identify participant characteristics associated with receipt of screening. Results: Of the 117 participants who completed the questionnaires, 43.6% were 50 to 60 years old, 36.8% identified as white, and 51.3% identified as non-Hispanic. The most common barrier to colonoscopy was the need for extensive bowel preparation (30.8%). For stool tests, common barriers included handling stool (20.5%) and not understanding how to do the test (20.5%). For virtual colonoscopy, barriers included the need for extensive bowel preparation (21.4%) and cost (21.4%). Most participants (67.5%) believed that they should know about all CRC screening options available, and their importance. The majority of participants (68.4%) preferred to learn about CRC screening from their doctor or healthcare provider. Younger age was associated with non-screening. Conclusion: We observed that study participants faced procedural barriers to complete CRC screening and preferred to learn about CRC screening options through their providers. Younger age groups were less likely to receive screening within our study sample. Future, targeted interventions to increase CRC screening should focus on increasing the awareness of the importance of CRC screening and educating patients on the various screening options available and their benefits, especially as they pertain to less invasive tests and targeting younger individuals.